2008
DOI: 10.1002/ijc.23355
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a novel docetaxel sensitizer, garlic‐derived S‐allylmercaptocysteine, as a treatment option for hormone refractory prostate cancer

Abstract: The recent introduction of docetaxel in the treatment of hormone refractory prostate cancer (HRPC) has made a small but significant impact on patient survival. However, its effect is limited by intolerance and resistance. The aim of our study was to investigate if the garlic-derived compound, S-allylmercaptocysteine (SAMC), was able to act as a docetaxel sensitizing agent. First, the effect of SAMC on docetaxel sensitivity was examined on 3 HRPC cell lines by colony forming assay. We found that SAMC increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 41 publications
(60 reference statements)
1
25
0
Order By: Relevance
“…In addition, the combination of docetaxel, vinorelbine and oral estramustine was a well-tolerated regimen with high biochemical and objective response rates in patients with androgen-resistant prostate cancer (ARPC) (Rosenberg et al, 2009). Very similar to our finding, garlic-derived S-allylmercaptocysteine augmented docetaxel-induced effect on growth inhibition of cultured PC3 and DU145 cells, and this combination effect was greater and synergistic (Howard et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the combination of docetaxel, vinorelbine and oral estramustine was a well-tolerated regimen with high biochemical and objective response rates in patients with androgen-resistant prostate cancer (ARPC) (Rosenberg et al, 2009). Very similar to our finding, garlic-derived S-allylmercaptocysteine augmented docetaxel-induced effect on growth inhibition of cultured PC3 and DU145 cells, and this combination effect was greater and synergistic (Howard et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…1,2 Based on a previous study, the IC90 dosage of docetaxel for DU145 cells is 1.01 ng/mL. 33 However, in this study, 40 ng/mL of docetaxel was unable to induce any effect on the viability of the CSC-enriched population (Fig. 5).…”
Section: Discussionmentioning
confidence: 57%
“…5c). At a dosage of 40 ng/mL, which has been shown to induce apoptosis in DU145 cells, 33 docetaxel failed to induce any observable effect on prostasphere number, suggesting that CSC-enriched cells are highly resistant to docetaxel. However, c-T3 treatment was found to significantly decrease the spheroid number by more than 70% (Fig.…”
Section: C-t3 Effectively Eliminates Chemoresistant Cancer Stem-like mentioning
confidence: 98%
“…A similar pattern of modulations has been frequently reconfirmed in the instance of xenograft mice models of hepatocellular carcinoma (Zhang, Z.M. et al, 2007) and refractory forms of prostate cancer (Howard et al, 2008;Singh et al, 2008).…”
Section: Experimental Studiesmentioning
confidence: 54%
“…The modulation of both cellular targets may be implicated in the chemosensitization to the same treatment. Studies on docetaxel, a chemotherapeutic administrated to patients affected by hormonal or colon cancers, show that both mechanisms may be implicated in the ability of OSCs to modulate its activity (Ban et al, 2009;Cox et al, 2006;Howard et al, 2008). Cox et al, however, have shown that coadministration of garlic and docetaxel did not significantly affect the drug disposition in breast cancer patients but a reduction of its clearance in specific cases cannot be excluded (Cox et al, 2006).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%